(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
Keratitis by Acanthamoeba is a clinical condition whose incidence has been increasing recently due to the use of soft contact lenses. This article presents a case of a young user of such lenses who developed a cadre of keratitis initially diagnosed as herpetic keratitis. By not responding to treatment, it was determined as a definitive diagnosis of Acanthamoeba keratitis after establishing by direct microscopic observation of trophozoites of Acanthamoeba corneal scraping. The presence of this microorganism was confirmed by obtaining abundant motile trophozoites in Vero cell culture. After initiation of therapy with chlorhexidine digluconate and polyhexamethylene biguadine, a rapid clinical improvement was achieved. This finding constitutes the first case of Acanthamoeba keratitis in the Department of Quindío and the first report of successful medical treatment with these two products. It should be noted that in this case the etiologic diagnosis was two months after the onset of symptoms in part due to Acanthamoeba keratitis may look the same to other conditions by different infectious agents such as herpes viral or fungal. Due to the rarity of Acanthamoeba, ophthalmologists do not consider this diagnostic possibility.